Gastric Adenocarcinoma with Yolk Sac Tumor Differentiation and Liver Metastasis of Yolk Sac Tumor Component. (2nd November 2013) - Bihari, Chhagan; Rastogi, Archana; Chandan, K. N.; Yadav, Vikas; Panda, Dipanjan
Abstract : Gastric adenocarcinoma with yolk sac tumor (YST) differentiation has rarely been reported. We report a case of primary gastric adenocarcinoma with yolk sac tumor differentiation and liver metastases of the YST component in a 50-years-old patient. This was suspected due to high serum level of alpha fetoprotein in the presence of a gastric fundal tumor. Gastric carcinoma with yolk sac tumor component is a rare entity with a poor prognostic outcome.